Global Financial Stability Report, September 2005 : Aspects of Global Asset Allocation. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2005)
This paper analyzes aspects of global asset allocation. It examines how different institutional investors follow vastly different procedures when allocating assets, reflecting various time horizons, liability structures, and 'cultural backgrounds.' It aims to provide some insight into the decision-making process of investors. The paper highlights that understanding the basis for investor decisions is useful when analyzing their asset allocation decisions and related capital flows across borders and asset classes. The paper also discusses the implications for financial stability of proposals and potential changes in accounting policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet